Will Happiness-Trainings Make Us Happier? A Research Synthesis Using an Online Findings-Archive - Bergsma, Ad; Buijt, Ivonne; Veenhoven, Ruut (Frontiers in Psychology, 2020)
Most people want to be happy and many look out for opportunities to achieve a more satisfying life. Following a happiness training I one such option, but the effectiveness of such trainings is being questioned. In this research synthesis we assessed: 1) whether happiness training techniques add to the happiness of their users, 2) how much happiness training techniques add to happiness, 3) how long the effect of happiness training lasts, 4) what kinds of training techniques work best, and 5) what types of groups of people profit from taking happiness training. We took stock of the available research and found 61 reports of effect studies on different training techniques, which together yielded 179 findings. These findings are available in an online ‘findings archive’, the World Database of Happiness. Using links to this source allows us to condense all this information in a few tabular overviews, while providing the reader with access to much detail. Happiness training techniques seem to do what they are designed to do: 83% of the findings showed a gain in happiness, 5% no change and 12% a loss in happiness. The average effect of happiness training was approximately 5% of the scale range. We conclude that taking a form happiness training is advisable for individuals looking for a more satisfying life. Since happier workers tend to be more productive, organizations would be wise to provide such training techniques for their workforce.